2014
DOI: 10.3109/21691401.2014.955105
|View full text |Cite
|
Sign up to set email alerts
|

Influence of selected variables on fabrication of Triamcinolone acetonide loaded solid lipid nanoparticles for topical treatment of dermal disorders

Abstract: Aim of the study was to develop solid lipid nanoparticles (SLN) of triamcinolone acetonide (TA) and to study the effect of various process variables in order to optimize the formulation for effective delivery. Drug loaded SLNs were successfully prepared and characterized by TEM, XRD and DSC study. Process variables like surfactant concentration, drug concentration, lipid concentration etc. showed significant effect on the particle size and entrapment efficiency. SLNs exhibited prolonged drug release following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…The % EE equivalent to percentage of drug encapsulated within nanoparticles was determined by indirect method. CUR-SLNs dispersion (1.0 ml) were centrifuged at 17,000 rpm (32,368g) for 60 min using cooling centrifuge (Remi Elektrotechnik Ltd., REMI-C24 BL, Thane, Maharashtra, India), to distinct the lipid and aqueous phase [18,19]. The supernatant was diluted with methanol and analyzed by HPLC.…”
Section: % Ee and Drug Loadingmentioning
confidence: 99%
“…The % EE equivalent to percentage of drug encapsulated within nanoparticles was determined by indirect method. CUR-SLNs dispersion (1.0 ml) were centrifuged at 17,000 rpm (32,368g) for 60 min using cooling centrifuge (Remi Elektrotechnik Ltd., REMI-C24 BL, Thane, Maharashtra, India), to distinct the lipid and aqueous phase [18,19]. The supernatant was diluted with methanol and analyzed by HPLC.…”
Section: % Ee and Drug Loadingmentioning
confidence: 99%
“…NLC, as the second generation of lipid nanoparticles, consist of the mixture of solid lipid and liquid lipid. They not only possess the outstanding advantages of solid lipid nanoparticles, but also avoid the disadvantages such as drug leakage and low entrapment efficacy, which can be attributed to the incorporation of liquid lipid that breaks the ordered crystalline state of solid lipid and enlarges drug storage space (Iqbal et al 2012, Pradhan et al 2016. In addition, NLC possess a number of features advantageous for the topical route of application.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 1 , by increasing the concentration of Tween 80, particle size would be reduced in the lowest amount of GMS. This phenomenon is due to a further reduction in interfacial tension and enhanced stabilization of particles by reduction of aggregation tendency as the result of higher concentrations of the surfactant [ 43 ]. In contrast, it was observed that with increasing the amount of GMS, the effect was reversed, and therefore, in the highest amount of GMS, the smallest particle size was achieved in the lowest concentration of Tween 80 (i.e., 0.5%).…”
Section: Resultsmentioning
confidence: 99%